Two- year postoperative MRI appearances of anterior cruciate ligament hamstrings autografts are not correlated with functional outcomes, anterior laxity, or patient age. (2021) - Bouguennec, N.; Robinson, J.; Douiri, A.; Graveleau, N.; Colombet, P. D.
No abstract available